Identifikasi Bidang Gelincir Tanah Longsor Menggunakan Metode Geolistrik Konfigurasi Schlumberger di Perumahan Ayudia Semarang - Sumarli Sumarli; Rambu Ririnsia Harra Hau (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
This study aims to identify the potential for landslides in the Ayudia housing location, Semarang. The data obtained in this study were apparent resistivity data using the geoelectric resistivity method of the Schlumberger configuration. Measurements were carried out on two tracks, namely the first track with a stretch length of 150 m and electrode spacing of 10 m and the second track with a stretch length of 75 m and electrode spacing of 5 m. Res2dinv software was used to display the resistivity value on each track so that a color image is seen that describes the change in resistivity in each rock layer. The results of the study indicated the identification of the location of the slip plane on the first track with a layer that is suspected to be the slip plane, namely limestone with resistivity values (307-939) Ã¢âÂ¦m and is at a depth of (19,9-26.9) m. This layer had a higher resistivity contrast than the top layer of the slip plane in the form of sandstone which can store water content. Thus, it could be concluded that the first track identified the potential for landslides to occur.